Step-by-step explanation:
y - y1 = m (x - x1)
(y - y1)/m = x - x1
x - x1 = (y - y1)/m
x = (y - y1)/m + x1
therefore, answer is option C
Topic: Change of subject / coordinate geometry
If you like to venture further, feel free to check out my insta (learntionary). I'll be constantly posting math tips and notes! Thanks!
Answer:
UM... i think maybe 1850
Step-by-step explanation:
Answer:
-3, 1
Step-by-step explanation:
f(x) = 3(x − 1)(x + 3)
To find the x intercepts, set the equation equal to zero
0 = 3(x − 1)(x + 3)
Using the zero product property
x-1 = 0 x+3 =0
x=1 x=-3